Некоторые аспекты учебной деятельности студентов вуза при кредитной системе обучения - Иванова, Е.Н. (My University, 2013)
The article is devoted to the peculiarities of adoption of the credit technology of teaching in the institutes of higher education of the Republic of Kazakhstan. The attention is given to the considera- tion of the educational activity. Some components and principles of the students’ educational activity in the Universities are stated in the article.